(untitled) (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2025)
In the context of modern economic realities , informal remote employment is becoming an important component of the shadow economy. This work is carried out without official registration and is often not subject to taxation, which creates difficulties for government agencies in the field of control and taxation. Informal employment harms not only the economy, but also the social sphere, reducing the level of social protection for workers. This situation requires a detailed analysis and development of recommendations on the legalization of remote work in order to ensure a fair competitive environment for all participants in the labor market and increase the level of social responsibility. The Government needs to develop measures to integrate such workers into the formal economy, including creating suitable conditions for their employment, improving access to social guarantees and tax benefits. The legalization of this segment of the labor market will test its sustainability and increase tax revenues to the budget, which in turn will improve social programs and strengthen the country’s economic security.